Radiotherapy improves the outcomes of immunotherapy with Sintilimab in non-small-cell lung cancer: A real-world analysis - Li, Shuling; Chen, Kuifei; Yang, Meiwen; Hlaing, Swe Swe; Chen, Meng; Gu, Pinjun; Meng, Yinnan; Yang, Haihua (Frontiers in Immunology, 2022)
Introduction Radiotherapy may augment systemic antitumor responses to immunotherapy. We did a retrospective study to infer whether radiotherapy improves outcomes to immunotherapy in patients with stage III and IV non-small-cell lung cancer (NSCLC). Methods This retrospective study conducted at Enze Medical Center enrolled 259 patients with histopathology confirmed NSCLC from December 2018 to December 31, 2021. All were treated with Sintilimab, some patients received radiotherapy at an appropriate time point. Radiation type includes conventional radiotherapy and stereotactic body radiotherapy. The progression-free survival (PFS), and overall survival (OS) were the primary endpoint. Results A retrospective analysis was performed on 259 patients, of whom 140 had been treated with immunotherapy lonely and 119 had been remedied with immunotherapy plus radiotherapy. Baseline variables were well balanced between the two groups, including gender, age, smoking status, TNM staging, number of metastases, ECOG score, pathological type and lines of previous systemic therapy. The median PFS in the immunotherapy alone group was 5.00 months (95%CI 4.38-5.62) versus immunotherapy plus radiotherapy was 9.00 months (5.95-12.05; p<0.001). The median OS in the immunotherapy alone group was 16.00 months (12.59-19.42) versus immunotherapy plus radiotherapy was 30.00 months (20.75-39.25; p=0.027). PFS was finer in the radiotherapy plus immunotherapy group than the immunotherapy group alone in both stage III(P=0.0069) and Stage IV(P=0.006) patients. In the univariate analysis, radiotherapy, male, ECOG=0 and <2 lines of previous systemic therapy were connected with an observably better PFS (P<0.001; P=0.03; P=0.002;P=0.021). In a multivariate analysis, radiotherapy, ECOG=0 and <2 lines of previous systemic therapy were independent prognostic factors with a markedly better PFS (P<0.001; P=0.006;P=0.009). An univariate analysis, radiotherapy, male, stage III, non-metastasis, ECOG=0 and squamous carcinoma were associated with a significantly better OS (P=0.032, P=0.036,P=0.002,P<0.001,P=0.002,P=0.025). A multivariate analysis, non-metastasis was a standalone prognostic indicator with a significantly better OS (P=0.006). However, radiotherapy was a tendency indicator with a better OS (HR0.70 95% CI 0.47-1.06). There were also no obvious increases in adverse events in the combination group. Conclusions Radiotherapy with addition of immunotherapy was observably linked to a better outcome in patients with III and IV staging NSCLC.